2019
DOI: 10.1089/dia.2018.0298
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Basal–Bolus Therapy in Type 2 Diabetes: A Randomized Controlled Trial Comparing Bolus Insulin Delivery Using an Insulin Patch with an Insulin Pen

Abstract: Background: Barriers to mealtime insulin include complexity, fear of injections, and lifestyle interference. This multicenter, randomized controlled trial evaluated efficacy, safety, and self-reported outcomes in adults with type 2 diabetes, inadequately controlled on basal insulin, initiating and managing mealtime insulin with a wearable patch versus an insulin pen. Methods: Adults with type 2 diabetes ( n = 278, age: 59.2 ± 8.9 years), were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…Several studies have shown that introducing a prandial insulin as part of a basal-bolus regimen in type 2 diabetes is more effective than a basal-only regimen at improving HbA 1c , as it provides postprandial insulin coverage (6)(7)(8)(9). For optimal postprandial glucose (PPG) control, an ideal prandial insulin should match carbohydrate absorption by demonstrating faster absorption, more rapid onset, and shorter duration of action.…”
mentioning
confidence: 99%
“…Several studies have shown that introducing a prandial insulin as part of a basal-bolus regimen in type 2 diabetes is more effective than a basal-only regimen at improving HbA 1c , as it provides postprandial insulin coverage (6)(7)(8)(9). For optimal postprandial glucose (PPG) control, an ideal prandial insulin should match carbohydrate absorption by demonstrating faster absorption, more rapid onset, and shorter duration of action.…”
mentioning
confidence: 99%
“…Many treatment algorithms and clinical trials of T2DM with beta cell death have been proposed so far [31][32][33][34] . Basal-Bolus, Basal plus, Basal supporting oral therapy (BOT), premixed insulins and premixed insulin and GLP-1R agonist were reported to improve safety and efficacy of the patient treated mainly in out-patient clinic [35][36][37][38][39][40][41][42] .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing mealtime insulin patches and insulin pens observed comparable improvement in HbA1c, FPG, total daily insulin dose, basal insulin dose, body weight, and hypoglycaemic episodes. Patient reported outcomes slightly favoured patches with significantly increased overall satisfaction and ease of use [63]. However, currently the size of the insulin reservoirs may be considered a limitation of these insulin delivery patches.…”
Section: Mealtime Insulin Delivery Patchesmentioning
confidence: 98%
“…Even though clinical inertia may be strongly patient driven, it must not be neglected that HCPs also face certain barriers to initiate insulin therapy. These may include lack of time, resources, cost or insufficient experience/expertise with insulin therapy and/or insulin delivery devices [63]. An international survey confirmed that the main barriers for the initiation of insulin therapy include the lack of experience of HCPs with the available insulin preparations and lack of time available for patient education [64].…”
Section: Initiating Insulin Therapymentioning
confidence: 99%
See 1 more Smart Citation